Pelaksanaan Peraturan Jaksa Agung Nomor Per-005/A/Ja/03/2013 Tentang Standar Operasional Prosedur Pengawalan Dan Pengamanan Tahanan Di Wilayah Hukum Kejaksaan Negeri Padang - Marisa Jemmy; Eliza Octa Khairani (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
The escort and security of detainees is an important part of the law enforcement process, particularly at the prosecution and trial stages. To ensure the orderly implementation of these duties, the Attorney General has established Attorney General Regulation Number Per-005/A/JA/03/2013 concerning Standard Operating Procedures for Escorting and Securing Detainees. However, in practice, the implementation of this regulation still faces various obstacles, especially in work units with high caseloads and high numbers of detainees, such as the Padang District Attorney's Office. The problems examined in this research include: first, how is the implementation of Attorney General Regulation Number Per-005/A/JA/03/2013 concerning Standard Operating Procedures for Escorting and Securing Detainees in the jurisdiction of the Padang District Attorney's Office; second, what obstacles are faced in implementing this regulation; and third, what efforts are made to overcome these obstacles. In line with these problems, the purpose of this study is to determine and analyze the implementation of the Standard Operating Procedure (SOP) for escorting and securing prisoners, identify obstacles that arise in practice, and formulate efforts made by the Padang District Attorney's Office to optimize its implementation. This study uses a sociological juridical approach with a descriptive research nature. The data used consists of primary and secondary data. Primary data was obtained through direct interviews with authorized Padang District Attorney's Office officials involved in escorting and securing prisoners, while secondary data was obtained through a literature review of laws and regulations, official documents, and relevant legal literature. The collected data was then analyzed qualitatively using inductive reasoning. The results indicate that, normatively, the Padang District Attorney's Office has adopted Attorney General Regulation No. Per-005/A/JA/03/2013 as the primary guideline for implementing prisoner escort and security. However, empirically, its implementation has not been optimal. The main obstacles identified include the limited number of prisoner escort personnel, inadequate facilities and infrastructure such as prison vehicles, handcuffs, and prisoner uniforms, and the high number of prisoners required to be escorted each trial day. These conditions have the potential to increase the risk of security disturbances, including the possibility of prisoner escape. Efforts to address these obstacles include improving coordination with the police regarding escorts, implementing situational task allocations, and optimizing supervision during the trial process. Nevertheless, this study concludes that increased human resource support and infrastructure are needed to ensure the implementation of SOPs for prisoner escort and security and ensure a safe, orderly, and just trial